ANALISIS DIMENSI DAN TOLERANSI PADA PROSES REKONDISI SILINDER HIDROLIK ARM EXCAVATOR - sutoyo, edi (Universitas Ibn Khaldun Bogor, 2017)
Hydraulic Excavator PC1250 is one of the heavy equipment that is widely used to transport mining materials, stone, forest products, and the other. Arm PC1250 hydraulic cylinder is a component that functions in hydarulic excavator arm moves. Arm cylinder damage occurs after reaching 3346 hours of operating hours should be reach 6000 hours. This situation requires the cylinder repaired/reconditioned. The reconditioning process is done in PT